Penetrating Wound in the Skull by a Sharp Metal Object - Ahmad Faried; Priandana Adya Eka Saputra; Farid Yudoyono; Muhammad Zafrullah Arifin (Faculty of Medicine Universitas Padjadjaran, 2015)
Objective: Penetrating skull injury (PSI) is a neurosurgical emergencies. Most PSI cases reported were caused by gunshot wounds. Although the diagnosis and management of those cases has been described, the actual cases, especially in our center, were quite rare.Methods: A craniectomy debridement with a supine position was performed and removal of the object was achieved. Intraoperatively, we succed control the bleeding as expected.Results: The patient was operated and hospitalized in our center; physical examination revealed neurologically intact before and after the removal of the object. The patient was sent home without any neurological deficits or other complications.Conclusions: We reported a case of penetrating skull injury in a 5-year-old girl caused by a scissors. Penetrating skull injuries were interesting due to its mechanism, management and complications. Early diagnosis and appropriate treatment should resulted in good outcomes.Keywords: Penetrating skull injury, a sharp metal object DOI: 10.15850/ijihs.v3n2.588